Trilogy Halal Tourism Al Mulk - Irawati, Nining Winda; Bulutoding, Lince; -, Siradjuddin (ITB AAS INDONESIA Surakarta, 2024)
This study aims to synthesize QS. Al-Mulk 67:15 which was revealed to be the Al-Mulk Halal Tourism Trilogy which has a connection with the sharia economy; This study uses the Islamic paradigm with a synthesis approach, namely understanding the verses of the Koran as a social reality. QS-based theory formulation. Al-Mulk is done by understanding QS. Al-Mulk 67:15, then determines the premise, and formulates a theory subjectively. ; The concept of the resulting values consists of: (1) The value of monotheism in the management of tourist destinations as outlined in the Vision and Mission, destination objectives, the application of halal tourism regulations, and the application of monotheism values in the management of tourist destinations, (2) Must pay attention to halal value both from the substance and the method of acquisition, and (3) fulfilling the elements of accountability in managing tourist destinations to Allah, humans and nature.